Pediatric Biliary Atresia: Prenatal and Postnatal Risk Factors - Dina Aristiya Sumarno1 , Sjamsul Arief2 , Bagus Setyoboedi3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Biliary atresia is the most common cause of cholestasis in infants caused by intrauterineand neonatal inflammatory process leads to progressive biliary tract obstruction and fibrosis. Risk factorsare expected to contribute in the disease type. Many studies have been done to determine the risk factorsof biliary atresia. Yet, there is still limited information about risk factors in Indonesia. This study aims todetermine the risk factors contributing to biliary atresia in East Java, Indonesia.Methods: This cross-sectional study collected 219 medical record data of cholestasis patients during January2010 to April 2017 that met the inclusion criteria. 85 of them were diagnosed with biliary atresia. Selectedprenatal and postnatal risk factor were evaluated and analyzed.Result: There were significant results in maternal age on pregnancy (p= 0.009), parity (p= 0.035), andgestational age (p= 0.005) among 85 patients which were diagnosed with biliary atresia. The regression testshowed significant result on those 3 factors.Conclusion: Maternal age on pregnancy, parity, and gestational age are the prenatal and postnatal riskfactors that contribute to the biliary atresia incidence. These results are expected to be used as one of theproviding information regarding prenatal and postnatal risk factors for pediatric biliary atresia in East Java,Indonesia